First vertebrate tracks and palaeoenvironment in a MIS-5 context in the Doñana National Park (Huelva, SW Spain). (1st September 2020) - Neto de Carvalho, Carlos; Muñiz, Fernando; Galán, José María; Rodríguez-Vidal, Joaquín; Gómez, Paula; Toscano, Antonio; Ruiz, Francisco; Belo, João; Belaústegui, Zain; Cáceres, Luis Miguel; Finlayson, Geraldine; Finlayson, Stewart; et al.
Abstract: A Late Pleistocene surface full of tracks and trackways (named 'Matalascañas Trampled Surface') has been exposed at the base of the 'El Asperillo' cliff (Doñana National Park, Matalascañas, Huelva, southwestern Spain) as a result of recent storms. This surface has been identified as the bottom of the unit AU1, according to the local stratigraphic section, and originated during the marine stage MIS-5 (∼106 ± 19 kyr). This trampled surface records exceptional tracks and trackways of different terrestrial vertebrates. In particular, three morphotypes of tracks ascribed to Artiodactyla (the auroch Bos primigenius ? the red deer Cervus elaphus and wild boar Sus scrofa ), one to Elephantidae ( Palaeoloxodon antiquus ), one of Canidae ( Canis lupus ), and three to waterbirds (geese, Anserinae, and waders, Charadrii) have been identified. This ichnoassociation is characteristic of a shorebird ichnofacies. We interpret this trampled surface to have been related to puddled areas of shallow waters in an inter-dune position, similar to present day examples in the Doñana National Park. Highlights: The Late Pleistocene aeolian deposits on Matalascañas (SW Spain) contain abundant mammal and bird tracks and trackways. These deposits form a lower set of cliff-foot dunes and another of rampant sands. The fossil tracks and trackways are concentrated in two units dated by OSL in 106 ± 19 kyr (MIS 5). The tracemakers identified are artiodactils, elephants, wolves, waterbirds and shorebirds. The palaeoenvironmental interpretation of the surface is related to puddled areas of shallow waters in an interdune position.